Trends and Evolution Research on Digital-based Assessment: A Bibliometric Analysis using Scopus Database - Zafrullah Zafrullah; Alfian Ma'arif; Astri Wahyuni; Aditya Gusti Mandala Putra (Peneliti Teknologi Teknik Indonesia, 2026)
This study aims to map global research trends and the evolution of digital based assessment systems through a bibliometric analysis. Using the PRISMA protocol on the Scopus database, publications from 1977 to 2026 were identified, resulting in 3,725 initial documents, which were filtered based on document type (articles), subject area (computer science), and relevance criteria to obtain a final dataset of 312 studies. Data were analyzed using Bibliometrix (R) and VOSviewer to examine publication trends, collaboration patterns, and keyword evolution. The findings indicate that digital based assessment research has evolved from basic computer based testing toward more adaptive and intelligent systems, with a steady annual growth rate of 2.87%. The results also reveal increasing cross regional collaboration, particularly between European and Asian institutions, along with the dominance of high impact journals such as Computers and Education and Computers in Human Behavior. Furthermore, five main research dimensions were identified: system infrastructure, digital pedagogy, advanced psychometric analytics, virtual learning governance, and user psychological behavior. Recent trends highlight the integration of adaptive testing, machine learning, and deep learning to enhance assessment accuracy and academic integrity; however, challenges related to inclusivity, ethical considerations, and student well being remain significant. Therefore, future research should focus on developing intelligent, ethical, and inclusive assessment systems that balance technological advancement with human centered considerations.